1999
DOI: 10.3171/spi.1999.91.2.0200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mexiletine on lipid peroxidation and early ultrastructural findings in experimental spinal cord injury

Abstract: Object. The purpose of this study was to investigate the effect of mexiletine on lipid peroxidation and on ultrastructural findings after induced spinal cord injury (SCI). The authors also compared the activity of mexiletine to that of the well-known antioxidant, methylprednisolone sodium succinate (MPSS). Methods. Wistar rats were divided into seven groups, (Groups 1–7). Those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…However, at the end of the study the significantly lower levels of MDA in the MP+melatonin combined treatment group in comparison with the other treatment groups may be the result of additive or synergistic effects of different antioxidative mechanisms. This effect might be insignifi-cant for preventing the pathological process of the injury since maximum tissue destruction takes place immediately and continues for 24h after the injury [13,17]. Neurobehavioral, ultrastructural, and electrophysiological results of our study also support this opinion.…”
Section: Discussionsupporting
confidence: 79%
“…However, at the end of the study the significantly lower levels of MDA in the MP+melatonin combined treatment group in comparison with the other treatment groups may be the result of additive or synergistic effects of different antioxidative mechanisms. This effect might be insignifi-cant for preventing the pathological process of the injury since maximum tissue destruction takes place immediately and continues for 24h after the injury [13,17]. Neurobehavioral, ultrastructural, and electrophysiological results of our study also support this opinion.…”
Section: Discussionsupporting
confidence: 79%
“…Further, the ROS level measured in the control-uninjured group in our study is comparable with that of healthy tissue of other e ective in vivo models. 20,21 Our measurements also indicate that our in vitro experimental condition was su cient to sustain the functional integrity of the extracted tissue. For example, electrophysiological recording, using double sucrose-gap chamber, showed that the isolated spinal cord tissue, when no deliberate compression was performed, was functionally competent by the end of the maximal experimental period (4 h) (Figure 2).…”
Section: Discussionmentioning
confidence: 59%
“…20,21,32 For example, the LPO values range from about 6 ± 10 nmol/100 mg 20,21 to 158 nmol/100 mg 32 in the control. One possible explanation of such a phenomenon is the inability to standardize the experimental condition in these in vivo studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been a number of studies performed in an attempt to identify the pathophysiological mechanisms occurring after traumatic SCI. [12][13][14][15] Lipid peroxidation is one of the main pathological mechanisms involved in secondary damage after a SCI. The primary autodestructive event is started by the hydrolysis of fatty acids from membrane phospholipids, leading to cellular damage.…”
Section: Discussionmentioning
confidence: 99%